2021
DOI: 10.3390/min11111269
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Multiple-Sourced Cherts in Maokou Carbonates in Sichuan Basin, South China

Abstract: Cherts have been thought to originate from biosilicification, terrestrial inputs and hydrothermal activity. The study of cherts is helpful in understanding the paleo-ocean environment and tectonic–sedimentary processes. Large amounts of cherts occur widely in the Maokou Formation in the Sichuan Basin, which may be largely connected to the Permian Chert Event (PCE). However, the source of silica and the formation process of cherts remain debated. Here, we analyze the petrographic and geochemical features of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…During the sedimentation period of the Qixia Formation and Maokou Formation, the Sichuan Basin experienced open platform sedimentation, with certain regions featuring intra-platform shoals. Notably, the Qixia Formation exhibits relatively thick strata, often exceeding 100 m, while the Emeishan basalt is situated between the Middle and Upper Permian strata [8,15,19].…”
Section: Stratigraphy and Sedimentary Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…During the sedimentation period of the Qixia Formation and Maokou Formation, the Sichuan Basin experienced open platform sedimentation, with certain regions featuring intra-platform shoals. Notably, the Qixia Formation exhibits relatively thick strata, often exceeding 100 m, while the Emeishan basalt is situated between the Middle and Upper Permian strata [8,15,19].…”
Section: Stratigraphy and Sedimentary Environmentmentioning
confidence: 99%
“…Platform shoals, including the Changxing Formation, Feixianguan Formation, and Jialingjiang Formation, are also under exploration [10,11]. Additionally, exploration efforts extend to the Middle Permian shoals, encompassing the platform margins and gently sloping shoals of the Qixia Formation in the western and northwest regions of Sichuan [11][12][13][14][15][16]. It is noteworthy that the distribution of strata and reservoirs is largely governed by the sedimentary facies [2,6,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chert nodules and bedded chert are of great geological significance for their strong weathering resistance and various silica sources (Maliva et al, 1989;Sugitani, 1992;Racki, 1999;Beauchamp and Baud, 2002;Kato and Nakamura, 2003). A remarkable chert accumulation event, the "Permian Chert Event (PCE)", occurred in the Middle-Late Permian (Beauchamp and Baud, 2002;Yao et al, 2013;Gao et al, 2020;Yu et al, 2020;Zheng et al, 2021). The Permian cherts were distributed in the margin of the Pangea and the Paleo-Tethys realm (Beauchamp and Baud, 2002;Yao et al, 2013;Dong et al, 2020;Yao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The cold bottom seawater could be derived from glacier melting or wind-driven fluxes along the margin of the Pangea (Yu et al, 2020). It was also suggested that the PCE in the South China Block (SCB) might be triggered by various factors: 1) biologic origin, which became one of the most vital Si sources for cherts in the SCB, with the dramatic evolution of siliceous organisms (Beauchamp and Baud, 2002;Yao et al, 2013;Gao et al, 2020;Yu et al, 2020;Zheng et al, 2021); 2) tectonic activities, which could create extra space for crystal growth, elevate temperature, and induce silica-rich hydrothermal fluids that were saturated with respect to silica when moving up and precipitate as cherts (Dong et al, 2020;Yao et al, 2021); 3) the Emeishan Large Igneous Province (ELIP), which, evidenced by intense tectonic events and hydrothermal activities, is dated to 260 ± 3 Ma (Shellnutt, 2014) and might have led to formation of the PCE cherts (Dong et al, 2020;Zheng et al, 2021). However, there is no consensus on the Si sources of the PCE cherts.…”
Section: Introductionmentioning
confidence: 99%